Causal links between obesity, lipids, adipokines, and cognition: a bidirectional Mendelian-randomization analysis - Gong, Meng; Liu, Haichao; Liu, Zhixiang; Wang, Yongshen; Qi, Shiyi; Guo, Hong; Jin, Song (Frontiers in Endocrinology, 2025)
BackgroundThe aim of this study was to explore the genetic level association between obesity, lipids, adipokines, and cognitive ability using bidirectional Mendelian randomization (MR) strategies.MethodsSummary data for three obesity indicators [body mass index (BMI), body fat percentage (BFP) and waist-hip ratio (WHR)], three lipid indicators [HDL cholesterol (HDL), LDL cholesterol (LDL) and triglycerides (TG)], three adipokines [circulating leptin (LEP), Agouti-related protein (AgRP) and Adiponectin (APDN)], and four cognitive ability indicators [cognitive function (CF), cognitive performance (CP), simple reaction time (SRT) and fluid intelligence score (FIS)] were collected. Bidirectional inverse-variance weighted Mendelian randomization (MR) was employed to evaluate the relationship between adiposity and cognitive function. We employed genetic instruments for adiposity indicators as exposures in one direction, and repeated the analysis in the opposite direction using instruments for cognitive function. Sensitivity analyses were conducted to explore heterogeneity and potential horizontal pleiotropy.ResultsGenetically predicted adiposity showed robust associations with markers of cognitive ability. Higher genetically predicted obesity indicators (such as BMI, BFP and WHR), and lipid and adipokineslevels (such as HDL and AgRP) with reduced cognitive ability indicators (such as CF and CP). In the opposite direction, FIS and SRT may influence BMI and HDL respectively. MR estimates for the effects of cognition ability on all obesity, lipids and adipokines measures indicated worse FIS and SRT were associated with higher BMI and lower HDL.ConclusionsOur MR reveals that high BMI, BFP, WHR and AgRP have negative causal direct effects with cognitive ability, while high HDL and ADPN have positive causal direct effects with cognitive ability. For the reverse causal direction, our consistent findings that worse cognitive function such as SRT and FIS may influence serum HDL level and BMI.